Implementation of the Fuzzy Mamdani Method in Decisions on Light Intensity in Plant Seed Research Rooms: Implementasi Metode Fuzzy Mamdani dalam Keputusan Intensitas Cahaya Ruangan Penelitian Benih Tumbuhan - Wijanarko, Kukuh; Shaum, Amien; Yuniar Chairunisa, Dwi; Auzan Anshar, Muhammad; Cahyadi, Rizhan (Journal of Vocational Education and Information Technology (JVEIT), 2023)
This research is motivated by the assignment requirements of the intelligent systems course. Meanwhile, the title selection was based on the need for automatic regulation of the light intensity of the research lab room. The problem faced is that practitioners cannot regulate the light intensity at all times when there are changes in air temperature and humidity, then during the growth period the seeds must receive sufficient light so that seed growth can be maximized and can be predicted and managed well. This problem can be overcome one way by using the Fuzzy Mamdani method. The fuzzy mamdani method uses 3 variables, namely, input data, data rules, and output. The fuzzy input used in this research is the temperature and humidity values. The fuzzy rules applied are how the input value influences the output that will be produced. The output in this research is the size of the light intensity value. The use of the fuzzy application method is assisted by MATLAB Production Server R2015a 2.1 software. The fuzzy logic in the plant research room was successfully implemented and developed and produced accurate light intensity output, thereby helping practitioners to obtain optimal seeds. In this research, the Fuzzy Mamdani Method was used.